1971
DOI: 10.1351/pac197125030527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unshared pairs of electrons and their solvation on conformational equilibria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
1
2

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(126 citation statements)
references
References 0 publications
12
111
1
2
Order By: Relevance
“…Furthermore, it was found that ␣-glycosides (1,2-␣ ␣ cis-axial) were more labile than ␤-glyco-␤ sides (1,2-trans-equatorial). Generally it is accepted that ␣-anomers are thermodynamically more stable than ␣ ␣ ␤-anomer ␤ s [41][42][43], which is inconsistent with t t our observation in the low-energy CID process. Extensive theoretical calculations are under way to explain the phenomena.…”
Section: Erms Analysiscontrasting
confidence: 99%
“…Furthermore, it was found that ␣-glycosides (1,2-␣ ␣ cis-axial) were more labile than ␤-glyco-␤ sides (1,2-trans-equatorial). Generally it is accepted that ␣-anomers are thermodynamically more stable than ␣ ␣ ␤-anomer ␤ s [41][42][43], which is inconsistent with t t our observation in the low-energy CID process. Extensive theoretical calculations are under way to explain the phenomena.…”
Section: Erms Analysiscontrasting
confidence: 99%
“…The ac 4 conformation, I", is also observed to predominate for some c~-methyl ribopyranoside derivatives in non-polar solvents, by reason of this bonding O(2)H-..O(4)H interaction (cf. Lemieux, 1971). * However, this is not observed in this crystal structure; neither is there any evidence for an intramolecular hydrogen bond between the syn-axial groups O(3)H to O(1)-CH3 in I', which could provide additional stability for the Ca conformer.…”
Section: Resultsmentioning
confidence: 99%
“…In both structures, the conformation observed is consistent with the orientation favored by the 'exo-anomeric effect' (cf. Lemieux, 1971;Jeffrey, Pople & Radom, 1973). The bond distances and bond angles for I and II are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…It is exemplified by the effect of solvent on the 4C 1 ~ 1C4 pyranoside equilibrium shown below, as postulated by Lemieux (1971) from optical and n.m.r, studies.…”
Section: The Crystal Environment Of the Gluconate Ionmentioning
confidence: 88%